2015
DOI: 10.1016/j.cgh.2014.07.058
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit-to-Risk Balance of Combining Infliximab With Azathioprine Varies With Age: A Markov Model

Abstract: BACKGROUND & AIMS Combination therapy with infliximab and azathioprine has demonstrated benefit over monotherapy for moderate-to-severe Crohn’s Disease. Clinical trials and models have not accounted for age-specific risks associated with these therapies, including the risk of immunosuppression-related cancer and infection. After accounting for these risks, the strategy yielding the greatest benefit may vary with age. METHODS We assessed age-specific risks and benefits of combination therapy compared to infli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…In contrast, other than cervical cancer, 25 the risk of solid organ cancer development appears unaltered. However, despite the modest increase in risk of malignancy, the absolute risk of incident cancers in individuals with no prior cancer remains very low, providing reassurance regarding the wide spread use of such treatment strategies in the population 26, 27 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other than cervical cancer, 25 the risk of solid organ cancer development appears unaltered. However, despite the modest increase in risk of malignancy, the absolute risk of incident cancers in individuals with no prior cancer remains very low, providing reassurance regarding the wide spread use of such treatment strategies in the population 26, 27 .…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of contraindications, we recommend starting combination therapy with an anti-TNF and a thiopurine for patients with moderate-to-severe UC, with the recognition of the rare, but uniformly fatal risk, of hepatosplenic T cell lymphoma in young males, which may limit the acceptance of combination therapy by physicians and patients alike. This recommendation may be tempered by the greater risk of serious infection in the elderly populations in whom monotherapy with an anti-TNF drug may be more appropriate [36][37][38][39].…”
Section: Combination Therapymentioning
confidence: 94%
“…Young males with limited disease also cause some additional concern due to the risk of hepatosplenic T-cell lymphoma. Decisions need to be made individually, but for most patients who clinically require a combination therapy, the benefits will probably outweigh the risks [21] .…”
Section: Combination With Immunosuppressionmentioning
confidence: 98%
“…The Markov model analysis by Scott et al [21] demonstrated that the addition of an immunosuppressive drug to anti-TNF therapy increases treatment efficacy for infliximab in IBD, outweighing the additive risk. The use of combination therapy appears to add no significant risk for serious complications (e.g.…”
Section: Combination With Immunosuppressionmentioning
confidence: 99%